Optimization of laser show projection - 443313 Muhammad Khairul Osman; Rosly Abd. Rahman, supervisor; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains (Fizik)) - Universiti Teknologi Malaysia, 2009